Dynamic domain decomposition strategy coupling lattice Boltzmann methods with Finite differences approximations of the Navier-Stokes equations to study bodies in current - Colicchio, Giuseppina; Greco, Marilena; Lugni, Claudio; Faltinsen, Odd Magnus (Volume 11: Prof. Robert F. Beck Honoring Symposium on Marine Hydrodynamics, 2015)
A Domain-Decomposition (DD) strategy is proposed for problems involving regions with slow variations of the flow (A) and others where the fluid features undergo rapid changes (B), like in the case of steady current past bodies with pronounced local unsteadiness connected with the vortex shedding from the structures. For an efficient and accurate solution of such problems, the DD couples a Finite Difference solver of the Navier-Stokes equations (FD-NS) with a Multiple Relaxation Time Lattice Boltzmann method (MRT-LBM). Regions A are handled by FD-NS, while zones B are solved by MRT-LBM and the two solvers exchange information within a strong coupling strategy. Present DD strategy is able to deal with a dynamic change of the sub-domains topology. This feature is needed when regions with vorticity shed from the body vary in time for a more flexible and reliable solution strategy. Its performances in terms of accuracy and efficiency have been successfully assessed by comparing the hybrid solver against a full FD-NS solution and experimental data for a 2D circular cylinder in an impulsively started flow. publishedVersion (c) 2015 by ASME